Information Exchange at a Distance: Examining the Influence of Leadership on Knowledge Sharing in Virtual Teams. Issue 2 (3rd April 2021) - Singh, Rajesh
ABSTRACT: Knowledge sharing and collaborative exchanges are crucial points of study in the current technological and informational climate within higher education. Factors that affect the practice of knowledge sharing have been extensively studied, with attention paid to the theme of leadership. This exploratory study examines the influence of leadership on knowledge creation within the virtual team projects of 169 library and information (LIS) students in an academic context. The perceived quality of knowledge creation was measured and analysed into three levels: enhanced, moderate and baseline. The findings reveal underlying factors that could contribute the emergence of self-emerged leadership in virtual teams. Furthermore, the findings emphasise that it is important to take into consideration the nuances of virtual collaborative environments while devising virtual team management strategies.